THE EFFECT OF PRODUCT QUALITY AND AFTER-SALES SERVICE ON CUSTOMER LOYALTY OF XIAOMI SMARTPHONE USERS IN MEDAN CITY - Sjukun Sjukun (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research aims to analyze the effect of product quality and after-sales service on customer loyalty among Xiaomi smartphone users in Medan City. The study employed a quantitative explanatory design with purposive sampling, involving 100 respondents who had been using Xiaomi smartphones for at least six months. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that both product quality and after-sales service have a significant and positive impact on customer loyalty. However, after-sales service emerged as the dominant factor, as indicated by a higher path coefficient and effect size compared to product quality. This suggests that warranty claims, repair services, availability of spare parts, and responsiveness of customer support are crucial determinants of long-term loyalty in the highly competitive smartphone market. The model explains 57.5% of the variance in customer loyalty, which indicates a moderate to strong predictive power. The findings extend previous research by highlighting the importance of post-purchase services in shaping loyalty, especially in emerging markets. For practitioners, the results provide strategic implications, emphasizing that while product quality should remain a priority, greater investment in after-sales infrastructure and proactive customer engagement will yield stronger loyalty outcomes for Xiaomi in Medan City.